Hubungan Antara Status Gizi dengan Siklus Menstruasi dan Dismenorea Pada Remaja Putri - Dewi, Ni Made Risma; Afsah, Yusi Riwayatul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Background: Nutritional status will affect the formation of hormones involved in the menstrual process such as FSH, LH, estrogen and progesterone hormones. Adolescents with less or more nutrition will have an impact on reproductive disorders including the menstrual cycle and also dysmenorrhea. Aims: Knowing the relationship between Nutritional Status with Menstrual Cycle and Dysmenorrhea Methods: This research uses analytic observational method with cross sectional approach. The population of this research is all students of Madrasah Aliyah Negeri 02 Yogyakarta class X, XI academic year 2021/2022, with a sample of 72 people. Inclusion criteria are students aged 15-18. Exclusion criteria were experiencing reproductive disease and smoking. The sampling technique is probability sampling by means of simple random sampling. Results: The results showed that 36 female students (50.0%) had normal nutritional status, 42 female students (58.3%) experienced normal menstrual cycles, and 53 female students (73.6%) experienced dysmenorrhea. Statistically with the Spearman Rank test, it was found that nutritional status had a relationship with the menstrual cycle, P value = 0.003 (p <0.05), then the results also showed that nutritional status did not have a correlation with dysmenorrhoea which showed P value = 0.25 (p>0 ,05). Conclusion: There is a relationship between nutritional status and menstrual cycle in Adolescent Girls at Madrasah Aliyah Negeri 02 Yogyakarta. There is no relationship between nutritional status and dysmenorrhea in Adolescent Girls at Madrasah Aliyah Negeri 02 Yogyakarta.